PENGARUH PROJECT BASE LEARNING TERHADAP KETERAMPILAN CRITICAL THINKING AND COLLABORATION PADA PRAKTIK PEMESINAN BUBUT DI SMK NEGERI 1 CILEGON - Sabirin, Sahril; Atep Iman; Moh Fawaid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocational learning in vocational high schools (SMK) needs to develop 21st-century skills, particularly critical thinking and collaboration skills. However, practical learning is still often teacher-oriented, so student active involvement is not yet optimal. Project-Based Learning (PjBL) is a learning approach that emphasizes student involvement through the completion of real projects. This study aims to analyze the effect of PjBL on students' critical thinking and collaboration skills in lathe machining practical learning at SMK Negeri 1 Cilegon. This study uses a quantitative approach with an ex post facto design. The research sample consisted of 72 students from the Machining Engineering program, selected through purposive sampling. Data were collected using a closed questionnaire that had been tested for validity and reliability. Data analysis was performed using simple linear regression with the help of IBM SPSS. The results showed that Project-Based Learning had a positive and significant effect on critical thinking skills with a contribution of 16% and on collaboration skills with a contribution of 27.9%. These findings confirm that PjBL is effective in improving critical thinking and collaboration skills among vocational high school students, especially in practical learning. This study provides empirical contributions to the development of vocational learning oriented towards work readiness and 21st-century skills.